Nicotinic acetylcholine receptors and epilepsy - Andrea Becchetti; Laura Clara Grandi; Marta Cerina; Alida Amadeo (Elsevier, 2023)
Despite recent advances in understanding the causes of epilepsy, especially the genetic, comprehending the biological mechanisms that lead to the epileptic phenotype remains difficult. A paradigmatic case is constituted by the epilepsies caused by altered neuronal nicotinic acetylcholine receptors (nAChRs), which exert complex physiological functions in mature as well as developing brain. The ascending cholinergic projections exert potent control of forebrain excitability, and wide evidence implicates nAChR dysregulation as both cause and effect of epileptiform activity. First, tonic-clonic seizures are triggered by administration of high doses of nicotinic agonists, whereas non-convulsive doses have kindling effects. Second, sleep-related epilepsy can be caused by mutations on genes encoding nAChR subunits widely expressed in the forebrain (CHRNA4, CHRNB2, CHRNA2). Third, in animal models of acquired epilepsy, complex time-dependent alterations in cholinergic innervation are observed following repeated seizures. Heteromeric nAChRs are central players in epileptogenesis. Evidence is wide for autosomal dominant sleep-related hypermotor epilepsy (ADSHE). Studies of ADSHE-linked nAChR subunits in expression systems suggest that the epileptogenic process is promoted by overactive receptors. Investigation in animal models of ADSHE indicates that expression of mutant nAChRs can lead to lifelong hyperexcitability by altering i) the function of GABAergic populations in the mature neocortex and thalamus, ii) synaptic architecture during synaptogenesis. Understanding the balance of the epileptogenic effects in adult and developing networks is essential to plan rational therapy at different ages. Combining this knowledge with a deeper understanding of the functional and pharmacological properties of individual mutations will advance precision and personalized medicine in nAChR-dependent epilepsy.